The upright brush : Yan Zhenqing's calligraphy and Song literati politics - McNair, Amy; Yan, Zhenqing, 709-785. (Honolulu : University of Hawai'i Press, 1998)
In the history of Chinese calligraphy, few are more famous than the eighth-century statesman Yan Zhenqing (709-785). His style is still taught today as a standard, and Chinese bookstores the world over stock inexpensive reproductions of his works for sale as copybooks. Yet Yan's style cannot be called conventionally attractive. "Correct," "severe," "serious," "forceful" are terms habitually applied to describe his writing--rarely has his calligraphy been called graceful or beautiful. How, then, did Yan earn such an eminent place in the history of art? In The Upright Brush, Amy McNair argues for the political rather than purely aesthetic basis for Yan Zhenqing's artistic reputation. She shows how his prominent position was made for him in the eleventh century by a handful of influential men who sought to advance their own position by associating themselves with Yan's reputation for uprightness. Equating style with personality, they adopted Yan's calligraphic style as a way to clothe themselves in his persona. Sophisticated, informed, and intelligent, The Upright Brush illuminates an episode (one of many) in the history of Chinese culture where the creative reinterpretation of the past was used for contemporary political means. It will be eagerly welcomed by all scholars of Chinese culture and history, as well as by those interested in the making and reading of art
Frontmatter -- Contents -- List of Figures -- Acknowledgments -- Introduction -- 1. The Politics of Calligraphy -- 2. Yan Zhenqing's Illustrious Background and Early Career -- 3. "The Nest Tipped and the Eggs Overturned": The An 3. Lushan Rebellion -- 4. Partisan Politics at the Postrebellion Court -- 5. From Daoist Inscriptions to Daoist Immortal -- 6. Buddhist Companions and Commemoration -- 7. The Late Style of Yan Zhenqing -- 8. Confucian Martyrdom -- Notes -- Glossary -- Bibliography -- Index -- About the Author
Originally presented as the author's thesis (Ph. D.--University of Chicago, 1989) under the title: The politics of calligraphic style in China.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Yan, Zhenqing, -- 709-785 -- Criticism and interpretation; Yan, Zhenqing, -- 709-785; Calligraphy, Chinese -- History -- Tang-Five dynasties, 618-960 -- Political aspects; Calligraphie chinoise -- Histoire -- 618-960 (Dynastie des Tang et les Cinq Dynasties) -- Aspect politique; ART -- Techniques -- Calligraphy; Kalligrafie; Chinees schrift; 618 - 960; Criticism, interpretation, etc; History